PENERAPAN PENDEKATAN SAINTIFIK MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BAHASA INGGRIS SISWA KELAS X IPA 1 SMA NEGERI 12 BANDAR LAMPUNG - Alia, Mis (Lentera: Jurnal Ilmiah Kependidikan, 2019)
This research aims to improve the activities and learning outcomes of students of class X IPA 1 of SMAN 12 Bandar Lampung through Discovery Learning by applying a scientific approach. This study used Classroom Action Research that has stages of planning, implementation, observation, and reflection, carried out in two cycles, each cycle conducted in two meetings. The results showed an increase in student activity and learning outcomes. Assessment of observations of learning activities also increased where in the initial condition 14 students or 43.75% increased to 25 students or 78.13% and 100% in the second cycle, while student learning outcomes showed an increase from the initial condition average value of 66.25 in the first cycle the average value obtained by students was 72.50 and in the second cycle the average value obtained by students was 78.13 with mastery learning from 16 students or 50.00% increased to 26 students or 81, 25% and 93.75% or 30 students in the last cycle.